Nivel de Riesgos De Factores de Deserción Escolar en Estudiantes Vinculados a Centro Etnoeducativo de Riohacha (2021)
The purpose of the following research project is to investigate the level of risks of Factors of school dropout in students linked to the Ethnoeducational Center of a Wayuu Community of the Riohacha Tourist District, taking into account that success or failure of boys, girls in training entities, includes an arduous procedure where there is a confluence of multiple elements of nature, family, social, cultural, material and personal that are simultaneously strengthened and impacted.